One Health studies of pig associated zoonoses in smallholder pig production in Lao PDR - Inthavong, Phouth; Khamlome, Boualam; Solomon, V.; Vongxay, K.; Allen, J.; Okello, A.; Conlan, J.; Gilbert, Jeffrey; Unger, Fred (2016)
Most people in rural areas of Lao PDR are living in close proximity to their livestock which may increase risk of being infected with pig zoonoses, either via direct contact with livestock, via consumption of contaminated pig products or mosquito vectors. Between 2006 and 2015 two ACIAR and one ILRI funded research projects were implemented in collaboration with animal and human health authorities of the Lao Government to study seroprevalence of pig production diseases and zoonoses. Overall 2341 human and 1356 pig serum samples were randomly collected from 81 villages in 8 provinces as well as from slaughterhouses. Pig samples were tested for zoonoses (Hepatitis E, Trichinella, Japanese Encephalitis and Cysticercosis) and some production pathogens; while human samples were tested for Hepatitis E, Trichinella, Japanese Encephalitis, Cysticercosis and Taeniasis. Results demonstrated the presence of in some cases high sero-prevalence of targeted pathogens among sampled human and pigs. Series of statistical analysis were performed to assess the risk factors and their association with any pathogens among pigs and human. The projects generated recommendations for control and future research, produced IEC materials, conducted public awareness and communication campaigns, and implemented intervention models for some diseases, and a number of articles published.